Serum Chloride Level Is Associated With Abdominal Aortic Calcification - Hu, Sheng; Lan, Tian; Wang, Silin; Su, Lang; Zou, Sheng; Ye, Jiayue; Zhang, Yang; Zhang, Deyuan; Guo, Qiang; Zhang, Wenxiong; Yu, Dongliang; Xu, Jianjun; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Abdominal aortic calcification is a potentially important independent risk factor for cardiovascular health. The aim of this study was to determine the relationship between serum chloride level and abdominal artery calcification. Methods: We obtained the data of 3018 individuals from the National Health and Nutrition Examination Survey database and analyzed the relationship between serum chloride and abdominal artery calcification. We performed stratified and single factor analysis, multiple equation regression analysis, smooth curve fitting, and threshold effect and saturation effect analysis. R and EmpowerStats were used for data analysis. Results: Serum chloride is independently related to the AAC total 24 score (AAC-24). The smooth curves fitted were all inverted-U shaped. Below a cutoff value of 92 mmol/L, increase in serum chloride level was associated with increase in AAC-24; however, above that cutoff, increase in serum chloride level was associated with decrease in AAC-24. Conclusions: At serum levels below 92 mmol/L, chloride is a risk factor for abdominal aortic calcification but levels above 92 mmol/L appear to protect against abdominal aortic calcification.